1996
DOI: 10.1101/lm.2.6.299
|View full text |Cite
|
Sign up to set email alerts
|

Integration of olfactory information in a spatial representation enabling accurate arm choice in the radial arm maze.

Abstract: The aim of the present study was to determine whether and how rats can use local olfactory cues for spatial orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…This study is, in fact, not the first example of illumination levels critically affecting the use of olfactory cues. Experiments run in a radial-maze in either the light or the dark, and with either the presence or absence of additional olfactory cues, clearly showed how olfactory cues were only used to guide accurate arm choice when the rats were in the dark (Lavenex and Schenk 1995). Likewise, previous studies have shown how visuospatial cues can outweigh olfactory cues when the two are in conflict (Olton and Collison 1979;Suzuki et al 1980).…”
Section: Discussionmentioning
confidence: 95%
“…This study is, in fact, not the first example of illumination levels critically affecting the use of olfactory cues. Experiments run in a radial-maze in either the light or the dark, and with either the presence or absence of additional olfactory cues, clearly showed how olfactory cues were only used to guide accurate arm choice when the rats were in the dark (Lavenex and Schenk 1995). Likewise, previous studies have shown how visuospatial cues can outweigh olfactory cues when the two are in conflict (Olton and Collison 1979;Suzuki et al 1980).…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, despite their increased exploratory behavior, women did not prove to be any less accurate in our spatial task: females first identified the rewarded locations, and then continued exploring the arena. If subjects had not been allowed to explore the environment after finding the rewards, some might have done so before focusing on the experimenter-defined 'goal' of the task [27,29]. Under such conditions, females' increased exploratory behavior might have thus led to an increase in the number of "errors" prior to finding all the rewards, resulting in poorer performance on the task as compared to males.…”
Section: Are There Gender Differences In Spatial Relational Learning mentioning
confidence: 99%
“…Under these conditions, rats will track an odor trail to a goal (34), even underwater (35). They can also orient to an array of odorant sources and will do so in the absence of visual cues (36). As they mature, however, rats require visual cues to orient in a lighted maze, even in the presence of learned olfactory cues.…”
Section: Mammalsmentioning
confidence: 99%